Event-related brain potentials reveal differences in emotional processing in alexithymia. Issue 5 (18th August 2019) - Jardin, Elliott; Allen, Philip A.; Levant, Ronald F.; Lien, Mei-Ching; McCurdy, Eric R.; Villalba, Anthony; Mallik, Peter; Houston, James R.; Gerdes, Zachary T.
ABSTRACT: The inability to recognise and describe emotions in the self is known as Alexithymia. In the present study we used event-related potentials (ERPs) to examine the locus of processing emotional differences in alexithymia. We tested men, both those scoring high (score > 61) and controls who scored low (score < 51) on the Toronto Alexithymia Scale-20 on an emotional face discrimination task. We assessed three ERP components: P1 (an index of early perceptual processing), N170 (an index of early facial processing) and P3 (an index of late attentional suppression). While controls showed a stronger P3 effect for angry faces relative to happy and neutral faces, Alexithymic men showed no significant differences in P3 across emotions. Alexithymic men showed delayed P1 and N170 amplitudes compared to controls. These results suggest that the locus of processing differences between alexithymic men and controls occur both early in perceptual processing and later in conscious processing.